Tipe kepribadian ekstraversi dan risk taking behavior remaja - Permadi, Dimas Agil (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Risk taking behavior in adolescents often gets them involved in various kinds of problems such as health, social sanctions and even legally. Extraversion is considered to be a predictor of risky behavior. Adolescents with extraversion tend to need more interaction with their external environment and also have a need to seek sensation. This study aims to determine the relationship between extraversion and risk-taking behavior in adolescents using a correlational quantitative method. The sample in this study were 194 adolescents and used the Google form as a data collection medium. The risk-taking behavior scale was compiled based on aspects of Weber and Blais and the extraversion scale used Eysenck's aspects which were then analyzed using SPSS 20. This study shows the results that extraversion has a positive relationship with risk-taking behavior in adolescents as indicated by the correlation value (r) 0.607 and a sig, ( p) 0.000.